Greek democracy and constitutional systems ( Athens as a model) - حسان علي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The systems of government in Greece developed and crystallized starting from the seventh century BC. After the Greeks lived under the tribal system, in which the chief of the tribe or the king was their supreme authority, this system developed into several systems that followed until it reached the democratic system in the fifth century. BC،These regimes did not appear sequentially in all the Greek city-states, but rather their development was shaped according to their social and economic conditions that they went through. Other cities settled in their development to the rule of tyranny until they deteriorated or remained as they are, and there are cities in which no political development took place due to their social and economic formations، Several political leaders who played important roles in the political life of Greece were famous, such as Solon, Cleisthenes, and Pericles.